TAMAN SARI ARTIFACTS IN PROBLEM BASED LEARNING: CULTIVATING MATHEMATICAL LITERACY THROUGH ETHNOMATHEMATICS - Dika Dwi Meilina; Marsigit (Ethnomathematics Journal, 2025)
This study aims to improve the mathematical literacy of eighth-grade students through the implementation of a problem-based learning model based on ethnomathematics, utilizing Taman Sari artifacts. This study is a classroom action research carried out in 2 cycles. Each cycle consists of planning, action, observation, and reflection. The subjects were 30 of eighth-grade students at a school in Bantul. Research data were obtained through tests, interviews, and documentation. Data were analyzed using qualitative descriptive analysis techniques. Data validation employed method triangulation techniques. The study results demonstrated an increase in students’ mathematical literacy after applying the problem-based learning model based on Taman Sari ethnomathematics. Specially, significant improvements were observed across all key mathematical literacy indicators, including formulate indicator (formulating problems), employ indicator (applying the concepts), and interpret indicator (interpreting and evaluating) with consistent progress noted from Cycle I to Cycle II. Based on these findings, it can be concluded that the application of a problem-based learning model based on Taman Sari ethnomathematics significantly improved students’ mathematical literacy in mathematics lessons, particularly in the Pythagorean theorem material.